Towards an Holistic Approach to Professional Learning and Development - Geoff Chivers; Graham Cheetham (Adult Education Research Conference, 2000)
This paper outlines research conducted by the authors between 1994 and 1999 into the nature of professional competence and how it is acquired. It discusses some of the key results which appear to suggest partiality both in existing models of professional competence and approaches to professional development.